2012
DOI: 10.1016/j.aprim.2011.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Ensayo clínico aleatorio: papel de la dieta y ejercicios físicos en mujeres con síndrome metabólico

Abstract: We demonstrated the effectiveness of the intervention program on blood pressure and blood lipid profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
4
0
4
Order By: Relevance
“…Study characteristics and descriptions of the interventions and main findings of eligible studies are summarised quantitatively in Table 1 , and qualitatively reviewed in the appendix (pp 14-23). The majority of the eligible studies were published in the last decade, 2012-2022, (90%), and conducted in lower-middle (56%) 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 or upper-middle-income (44%) 23 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 countries. No eligible study was found in low-income countries.…”
Section: Resultsmentioning
confidence: 99%
“…Study characteristics and descriptions of the interventions and main findings of eligible studies are summarised quantitatively in Table 1 , and qualitatively reviewed in the appendix (pp 14-23). The majority of the eligible studies were published in the last decade, 2012-2022, (90%), and conducted in lower-middle (56%) 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 or upper-middle-income (44%) 23 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 countries. No eligible study was found in low-income countries.…”
Section: Resultsmentioning
confidence: 99%
“…Respecto a la variable colesterol el 86,1 % tienen adecuados niveles, el 13.9 % valores elevados que se encuentran sobre los 200 mg/día (9). En la Región Junín, las cifras de dislipidemias han ido en aumento debido a diversos factores entre los que citamos una dieta rica en grasas o carbohidratos y la falta de actividad física, por lo que la falta de actividad física ha demostrado que puede incrementar los niveles de colesterol HDL en varones adultos estudiados (10). Las investigaciones en los antecedentes presentados nos muestran que la actividad física en adultos sedentarios puede mejorar las condiciones del perfil lipídico, que en su mayoría se encuentra alterado constituyendo cuadros de dislipidemia.…”
Section: Discussionunclassified
“…Actualmente el Ministerio de Salud en el Perú muestra que existe un nivel de actividad física bajo, en general menor al 10% en la edad de 15 a 69 años. Además, por la baja actividad física se ha incrementado los niveles de sobrepeso y obesidad como consecuencia de la pandemia del COVID 19 (8).…”
Section: Introductionunclassified
“…The concept of consumption of vegetables and fruits was strengthened. 19 All activities were carried out at the Community Cultural Centre, with the exception of clinical, nutritional, anthropometric, and biochemical assessments, which were carried out in the Community Care Center.…”
Section: Methodsmentioning
confidence: 99%